Field notes contributed by Raymond L. Cummins, fall 1991 - Cummins, Raymond L.et al (1991)
List of birds and locations contributed by Raymond L. Cummins. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1991. Epson - sheet feed